Residents’ perception of tourism: a systematic review from 1978 to 2019 - Scalabrini, Elaine; Remoaldo, Paula (Bulletin of Geography. Socio-economic Series, 2022)
Residents are crucial stakeholders in tourism development and their perceptions towards this activity have been studied since the 1970s. Since then, studies in this area have expanded considerably, including review papers. The purpose of this paper is to evaluate this evolution and to explore critically methodologies applied in studies about residents´ perceptions towards tourism between 1978 and 2019 and published in the ten most impactful tourism journals according to the Scimago Journal Ranking (2018). In a total of 260 papers, the main results showed that Tourism Management was the journal with the largest number of papers published. Most studies were quantitative in nature and atheoretical. The Social Exchange Theory has been the theory most frequently applied to date. The papers focused on residents´ perceptions, specifically in tourism destinations, natural areas, events and mega-events. New lines of research in future studies about this subject are suggested to provide new perspectives in this study area.